Pengaruh Financial Knowledge Dan Financial Attitude Terhadap Perilaku Keuangan Melalui Mediasi Locus Of Control Pada Mahasiswa Di Kota Bengkulu - Rofidah Silitonga, Lydia; Idham Lakoni; Veny Puspita (STEKOM PRESS, 2023)
This research study aims to determine the effect of financialknowledge and financialattitude on financialbehavior through the mediation of locusof control instudents the city ofBengkulu. Thepopulation study were students in thecity ofBengkulu. From calculations using theformula where[21], theindicator is 24 x 10, thesample size for thisstudy was determined to be 240 respondents. Determination of thesample using non-probability samplingtechnique with purposive samplingtechnique, by determining the criteria of therespondent. Theresearch approach used is quantitativeresearch. The type of data used in this study is primary data, namely research dataobtained directly from originalsources (respondents). The research data was processed using thesmartPLS 3.0 analysis tool. The results of thisstudy indicate that financialknowledge can influence financialbehavior directly and cannotinfluence it indirectly or through locus ofcontrol mediation. FinancialAttitude Variable can influenceFinancial Behaviordirectly and can also influence indirectly through Locus OfControl. Lastly, the variables of financialknowledge and financial attitudes have influence on the financialbehavior variable. FinancialKnowledge and FinancialAttitude Variables can affect the LocusOf Control variable. Finally, the Locus OfControl variable can have a significant effect on the FinancialBehavior Variables.